1117 Associations Between Health Behaviors And Sleep Duration In Women With Depression. (27th May 2020) - Peprah, R; Jenkins, D; Donley, T; Sexias, A; Jean-Louis, G
Abstract: Introduction: Sleep duration can have important effects on health. Long and short sleep has been associated with negative health outcomes in women. Depression may aggravate an already impaired sleep quality. This study explored associations between sleep duration and depression in pregnant women. Methods: We analyzed data for adult women (n=9, 372) from the 2017 and 2018 National Health Interview Survey (NHIS), which is a nationally representative study of the US civilian non-institutionalized population. Sleep was categorized by short (≤6 hrs), normal/healthy (7-8 hrs), and long (≥9 hrs) sleep. Using STATA 15.0 for Windows, we report weighted frequencies and Chi-and square tests. Alpha of 0.05 was used for all significance levels. Results: Of the sample, 81.7% of the women were White, 10.6% were Black and 7.7% were other minorities. The mean age was 51.4±18.3. We found that the proportion of women who reported short sleep increased with age (p<0.000). Current drinkers (37%) had higher numbers of normal sleep than those who were former drinkers or abstainers (p<0.000). With respect to BMI, more obese women were short and sleepers (17% and 4% respectively), but women with normal BMI (19%) were normal sleepers (p<0.000). In short sleepers, more women had trouble falling asleep (13%) and staying asleep (17%), but reported not using medication and never feeling rested. Similar results were found for long sleepers. Higher proportions of normal sleepers reported not have trouble falling asleep (27%), staying asleep (26%), or using medication for sleep (40%) (p<0.000). However, of those who reported normal sleep, greater frequencies of working up feeling rested occurred only 3-6 times in the past week (p<0.000). Conclusion: In this study, women with depression self-reported more normal sleep duration. This finding is inconsistent with previous research. Whether this association is causal and what pathways explain this association is unknown. Support: This study was supported by funding from the NIH: R01MD007716, R01HL142066, K01HL135452, and K07AG052685.